Knowledge sharing factors among EIS students in a private university - Nuansomsri, Chuleekorn; Jantavongso, Suttisak (2016)
Knowledge Sharing (KS) plays a significant role in knowledge creation for students, especially at a territory level. For this reason, this study aims to explore the sharing of knowledge factors among undergraduate students in a Thai private university.50 students from Bachelor of Science Program in Enterprise Information Systems (EIS) were participated.The data collection took place in February and March 2016.This study was classified as non-experimental, quantitative research using a survey approach.Descriptive statistics, inferential statistics, and correlation statistics were employed as the data analysis methods. The findings revealed that ‘Perceived Usefulness’, ‘Technological’, ‘Individual’, ‘Classroom’, and ‘Intention to Share’ factors were statistically significant. Despite these results, ‘Organizational’ factor had no influence on sharing of knowledge among these group of students.